Completing a soundscape questionnaire reduces the psychological distance of sound and hearing. (November 2022) - Welch, David; Rana, Komal; Reddy, Ravi
Objective: People are often resistant to hearing-health education messages such as those aimed at the prevention of noise-induced hearing loss. This resistance may be due to psychological distance: the perceived relevance of hearing and awareness of sound to daily life. The soundscape is the internal, perceptual, experience of a sound environment. The objective of this study was to explore people's thought processes when completing a questionnaire designed to assess the soundscape and, in particular, to investigate whether the experience reduced psychological distance of sound and their hearing. Design: Semi-structured interviews and qualitative data analysis. Setting: Questionnaires were completed on personal phones in any environment participants wished. Interviews were conducted via online video connection. Method: A soundscape questionnaire was administered to a convenience sample of adult volunteers who were then interviewed about the experience of completing it, and how doing so had influenced their views of sound and their hearing. Results: Themes in three main areas were identified: the questions, which were found to be challenging but interesting; the soundscape, and the insights of participants about their own soundscape experience; and participants' new awareness of sound and their own hearing. Conclusion: The findings provide interesting feedback about the meaning of responses to the questionnaire and on how people thought while using it. Furthermore, the findings imply that bringing the soundscape to a person's conscious awareness may successfully reduce psychological distance for them about their hearing and may, therefore, be a useful preliminary to hearing-health education interventions.